Potential drug-drug interactions in elderly patients in a renal ward: a single-center retrospective study in Pakistan - Ahmad, Nouman; Ramadhan, Andika Yusuf; Mahmood, Asif; Faisal, Shah (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2024)
Background: The increasing prevalence of kidney disease among elderly populations has led to a rise in potential drug-drug interactions (pDDIs), particularly due to widespread polypharmacy use in this demographic. Objective: This study aims to retrospectively analyze pDDIs and identify their prevalence and associated factors among elderly patients in a renal ward. Methods: This retrospective observational study was conducted at Saidu Group of Teaching Hospital in Swat, Pakistan, from January to December 2022. Data were obtained from the Patients Records Office using a conventional paper-based record system. A sample of 43 elderly patients (age ≥60 years) was selected through consecutive sampling. Drug interactions were assessed using freely available online tools: Drugs.com and Medscape Drug Checker, selected for their user-friendly accessibility and suitability in resource-limited settings. Results: Among the 43 elderly subjects with balanced gender distribution, the mean age was 66.53 ± 7.68 years. Comorbidities were present in 74.4% of patients, and each patient was prescribed an average of 4.58 medications. According to Medscape, 62.79% of patients experienced one or more potential drug interactions, while Drugs.com identified interactions in 67.44% of cases. Notably, 15% of these interactions were classified as high-risk by both tools. Logistic regression analysis indicated a significantly higher risk of potential drug interactions with increasing numbers of prescribed medications (OR = 4.515, p = 0.033). Conclusion: This study identified a high prevalence of pDDIs among elderly patients with kidney disease in Pakistan. The majority had comorbidities necessitating multiple medications, thereby increasing the risk of adverse drug reactions (ADRs). Mitigating these risks requires accurate prescribing practices, reliable electronic surveillance systems, and clinical pharmacist support.